Joey : a baby koala and his mother - Bishop, Nic, 1955- (Scholastic Press, 2020)
It's an exciting morning for Joey the baby koala, high above the ground, in the shade of a eucalyptus tree, Joey the baby koala wakes up hungry! Crawling over his sleeping mom, Joey goes exploring ... only to find that his mother's arms is where he's supposed to be after all. Featuring simple text and stunning photographs of a rare interaction between a koala and her little one. Includes fun facts about koalas and their habitat.